Health Behavior on The Elderly at City of Makassar - Iqbal Ahmad; Mappeaty Nyorong; H.M. Tahir Abdullah (Journal of sciences and health, 2022)
Baground: Complaints of disease and multi-diagnosis of disease in elderly people is not separated from how lifestyle of the elderly such as diet and drink, physical activity, sleep patterns and other behaviors. The research aimed to analyze the health behavior of the elderly people dwelling in the working area of Public Health Centre (PHC) Sudiang, Biringkanaya District, Makassar City. Method: This was a qualitative research with case study approach. Data were collected through an interview, observation sheets and medical records. Informants were selected using the purposive sampling technique as any as 6 people. The data were then analyzed through the work procedures of data collection, reduction, and presentation, and conclusion presented in narrative form. Result: The research results indicates that the health aspects related to the lifestyle are the sleeping habit of less more than 7 – 8 hours a day, diet and drink patterns namely the healthy food consumption, physical activity to maintain fitness and physical health, and maintain body balance. Conclusions: Psychological aspects are self-confidence in carrying out the activity, not depending on the family members, mental disorders such as feeling lonely and anxious are not the informants’ burden. If those aspects are applied maximally, it is not necessary to be worried facing the old age. Key words: Health behavior, elderly people.